Description of immatures of Galeacius martini Schouteden (Hemiptera: Heteroptera: Scutelleridae) - Bianchi, Filipe M.; Garbelotto, Thereza A.; Campos, Luiz A. (Zootaxa, 2011)
Scutelleridae occur worldwide, and immature stages have been scarcely studied. Galeacius Distant is a Neotropical genus currently containing four species. Here the external morphology of immatures of Galeacius martini Schouteden is described. Adults and nymphs were maintained in laboratory and fed on branches of Miconia sellowiana with fruits. The egg of G. martini is semi-spherical, reddish brown, with reticulations surrounding smaller granulated sculpturing under scanning electron microscopy (S.E.M). The nymphs from first to fifth instar have a stridulitrum plus plectrum, and 2+2 trichobothria posterior to spiracles on abdominal sternites III–VII. The dorso-abdominal scent efferent system has an evaporatorium with two distinct mycoid sculpturing, and their are two types of peritreme on medial plates II and III in first and fifth instar. The color and chorion morphology may distinguish G. martini from other scutellerid eggs so far described. New descriptions of immatures of Scutelleridae are particularly desirable, mainly with emphasis some structures on S.E.M., as stridulatory devices, dorso-abdominal scent efferent system, and trichobothria, thus improving the knowledge about the taxon.